Advancing gender diversity in leadership: the role of work-life balance and gender participation in Ugandan public universities - Tushabe, Monica; Kyambade, Mahadih; Namatovu, Afulah; Oyella, Sheilla (Taylor & Francis Ltd, 2025)
Despite advancements in promoting gender equality in the workforce, women remain underrepresented in leadership positions across various organizations. Several studies have examined the relationship between women’s representation and work-life balance (WLB); however, limited attention has been given to the mediating role of gender participation. This study addresses this gap by expanding the congruity theory to assess the direct and indirect effects of work-life balance in public universities in Uganda, a context that has received minimal scholarly attention. A self-administered survey was conducted among 289 respondents using a convenience sampling technique. Structural and measurement models were analyzed using Smart PLS 4 software. The findings revealed that work-life balance directly influences women’s representation in leadership positions. Additionally, gender participation was found to mediate this relationship. These results highlight the importance of fostering inclusive and supportive work environments that accommodate diverse needs and promote women’s advancement into leadership roles. The study contributes to the existing body of knowledge by providing a nuanced understanding of the interplay between work-life balance, gender participation, and women’s representation. It further emphasizes the need to address systemic barriers and biases to enhance gender diversity and inclusion in organizational leadership. The findings offer practical recommendations for managers and policymakers to cultivate a supportive and inclusive organizational culture that values work-life balance and gender diversity. KEYWORDS Work-life balance;participation; womenrepresentation; leadership;congruity theory; Uganda